Recent developments in understanding the relationship between 22q11.2 Deletion Syndrome and psychosis - O’Rourke, Linda (Curr Opin Psychiatry, 2019)
PURPOSE OF REVIEW: Individuals with 22q11.2 Deletion Syndrome (22q11.2DS) have high rates of comorbid mental illness, particularly psychosis and schizophrenia. The purpose of this review is to summarise recent research in the area of 22q11.2DS and psychosis. RECENT FINDINGS: Research over the past year has identified negative symptoms, functional impairment, dysphoric mood and a childhood diagnosis of attention deficit hyperactivity disorder as important clinical predictors of psychosis risk in 22q11.2DS. As previously reported in non-deleted schizophrenia, recent studies have implicated neuroinflammation as a possible neurobiological mechanism for psychosis in 22q11.2DS. Recent neuroimaging findings suggest the cortex is significantly thinner in those with 22q11.2DS and psychosis compared to those without psychosis, replicating similar findings in non-deleted schizophrenia. Further data from the International 22q11.2DS Brain and Behavior Consortium has suggested that chromosomal microdeletions are significantly more likely to involve protein-coding genes and several rare copy number variants are associated with the presence of psychosis in deleted individuals. SUMMARY: There have been several significant recent advances to further characterise the high rates of psychosis in 22q11.2DS, to identify additional clinical predictors of psychosis and to increase our understanding of the neural substrate and genetic aetiology of psychosis in 22q11.2DS.